1989
DOI: 10.1111/j.1365-2427.1989.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

The susceptiblity of Keratella cochlearis to interference from small cladocerans

Abstract: 1. Even at high population densities (300-2000 ind. 1"'), only one of five small cladoceran species (adult body length <1 mm) significantly suppressed population growth of the rotifer Keratella cochlearis through interference (encounter) competition. At 500 ind. 1"', adults of D. ambigua (0.96 mm body length) imposed an instantaneous per capita death rate of 0.21 day-' on this rotifer. These short-term experiments may have underestimated cladoceran interference because newborn rotifers were rarely present.2. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…This pattern of decreasing susceptibility with increasing body size is consistent with previously published results. Adults of K. cochlearis were much less likely to be killed or eaten by Ceriodaphnia dubia than newborns (Gilbert & MacIsaac, 1989). Similarly, the susceptibility of three species of Keratella to D. pulex (c. 2.5 mm) decreased as the total body length of the species increased-from K. cochlearis f. tecta (105 lm) to K. cochlearis f. typica (130 lm) to K. testudo (160 lm) to K. crassa (190 lm); K. crassa was about ten times less susceptible than K. cochlearis f. tecta (Gilbert, 1988a).…”
Section: Resultsmentioning
confidence: 98%
“…This pattern of decreasing susceptibility with increasing body size is consistent with previously published results. Adults of K. cochlearis were much less likely to be killed or eaten by Ceriodaphnia dubia than newborns (Gilbert & MacIsaac, 1989). Similarly, the susceptibility of three species of Keratella to D. pulex (c. 2.5 mm) decreased as the total body length of the species increased-from K. cochlearis f. tecta (105 lm) to K. cochlearis f. typica (130 lm) to K. testudo (160 lm) to K. crassa (190 lm); K. crassa was about ten times less susceptible than K. cochlearis f. tecta (Gilbert, 1988a).…”
Section: Resultsmentioning
confidence: 98%
“…Also, when cladoceran biomass was used as a covariate in order to remove this source of variation, there was at best a small improvement in the overall fit of the ANOVA model (with the covariate, an ANCOVA model) and the biomass covariate was never significant. It has been shown (Burns & Gilbert, 1986b;Gilbert, 1988a;Maclssac & Gilbert, 1989) that interference of cladocerans on rotifers increases with cladoceran body size. and a similar phenomena appears to be operating with ciliates.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted by previous laboratory studies, this rotifer was suppressed by large Daphnia without evidence of the suppression of a shared algal resource. It has been demonstrated that at lengths less than 1.2 mm, Daphnia interference effects on K. cochlearis {tecla form) are negligible (Bums & Giibert, 1986b) and that K. cochlearis can coexist with or even exclude medium and small cladocerans (Maclssac & Gilbert, 1989). The mean size of D. galeafa mendofae (no more than 1310 nm) in the enclosure experiment is small enough that most members of the population may net have been capable of inflicting any direct mortality on K. cochlearis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, when cladocerans and copepods were simultaneously abundant, their top-down control on ciliates might have declined, as the total of both ciliate abundance and biomass were lower in CONTROL than in FILTER but were relatively higher than those in CLAD and COPE. This may have been caused by the interference and exploitative competition among the metazoan zooplankton groups (copepods, cladocerans, and rotifers) (Gilbert and MacIsaac 1989;MacIsaac and Gilbert 1991).…”
Section: Discussionmentioning
confidence: 99%